Spastic paraparesis caused by X-linked adrenoleukodystrophy mimicking vacuolar myelopathy in a human immunodeficiency virus patient: A case report. Issue 20 (May 2018) - Park, Jin-Sung; Park, Donghwi
Abstract: Rationale: Vacuolar myelopathy is one of most common cause of spastic paresis in patients with human immunodeficiency virus (HIV) infection. However, X-linked adrenoleukodystrophy (X-ALD), which is a metabolic disorder caused by impairment of peroxisomal beta-oxidation of very-long-chain fatty acids (VLCFA), also manifests as various neurological deteriorations including adult onset spastic paraparesis. To the best of our knowledge, there has been no report of newly developed spastic paresis due to X-ALD in a patient with HIV infection. Patient concerns: A 30-year-old male had presented with progressive spastic paraparesis for 1 year. Diagnosis: X-ALD. Intervention: Brain and spine magnetic resonance imaging (MRI), VLCFA, and genetic test. Outcomes: His spinal MRI mimicked vacuolar myelopathy, but he was finally diagnosed with X-ALD using the VLCFA and genetic test. Lessons: Although rare, isolated spastic paraparesis can occur in HIV patients; additional tests such as VLCFA can be useful for the differential diagnosis. More data are needed to understand the pathological mechanisms underlying the two diseases.